Aerodynamic problems of urban UAV operations - Kittiyoungkun, S (Cranfield University, 2011)
Unmanned Air Vehicles, UAVs are designed to operate without any onboard controllers. Consequently, they are considered to operate in a wide range of applications. Missions in undesirable conditions such as bad weather and/or highly unsteady gustiness could cause an unsuccessful operation. In many ways, aerodynamics is a key feature in the performance of UAVs such as influencing deformation vehicle, guidance and control. Two aspects of this research are, therefore, to understand flying conditions of UAVs in an urban environment and how the flying performance is affected by such conditions. The first objective relies on understanding air flow behaviour in the lower part of the urban environment which has the most important role on the response of UAVs. The second objective will be to look at the characteristics of a three-dimensional airfoil when it encounters an unsteady sinusoidal gust at different oscillation frequencies and freestream velocities. As the first step of the studies on the aerodynamic problem of UAV operations in the lower part of an atmospheric boundary layer in an urban environment, the boundary layer thickness in a suitable wind tunnel facility were the first experimental results obtained. Experimental measurements of the mean velocity profile in a turbulent boundary layer were investigated for three different floor roughness conditions as well as a smooth wall condition. As a result, three different boundary layer thicknesses were then classified depending on the wall surface roughness and a combination with turbulence generators providing a maximum thickness of 280 mm at the centre of the tunnel test section. However,the experimental investigations into the turbulent boundary layer over a rough wall have shown that the boundary layer thickness is dependent on the surface roughness and is different from that obtained under the smooth wall condition. An experimental study into a simulated urban flow regime was then carried out after the measurement of the boundary layer. Wind tunnel experiments on the airflow around a single and twin buildings including an investigation of the airflow between the gap of the buildings were obtained. Wind in the lower part of the atmospheric boundary layer is more a micro-scale problem which increases or decreases the wind speed induced by buildings nearby. The studies have found some strong concentrated vortices caused by the flow separation essentially independent of the nature of the upstream flow and usually as a direct result of the building geometry and orientation. As the measurement location increased further downstream from the back of the buildings, the concentrated vortices were found to be weak and disappeared into the wake region. Finally, an experiment was conducted using a sinusoidal gust generator to describe the effects of wind oscillation parameters such as oscillation amplitude, oscillation frequency and reduced frequency under static and dynamic conditions. An evaluation was made of the onset of dynamic stall due to rapid changes in angle of attack during an unsteady pitch motion. The NACA 23012 wing profile was tested at a fixed angle of attack condition with varying oscillation flow parameters. Results demonstrate that those parameters influence the dynamic stall and hysteresis loop based on lift coefficient and angle of attack